Effect of deposition power in fabrication of highly efficient CdS:O/CdTe thin film solar cell by the magnetron sputtering technique. (December 2015) - Islam, M.A.; Khandaker, M.U.; Amin, N.
Abstract: Polycrystalline II–VI semiconductor materials such as oxygenated CdS have a wide and tunable band gap (≥2.5 eV) which plays an important role in increasing the light absorption capacity of CdTe absorber. In this study, the ultra-thin CdS:O and CdTe films were deposited by the sputtering technique and the optimum condition of deposition power is investigated. The prepared ultra-thin films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX) analysis, X-ray photoelectron spectroscopy (XPS), UV–vis spectrometry, Hall Effect and current–voltage measurements techniques. The complete cell was then fabricated by the sputtering technique with a novel configuration of 'glass/FTO/ZnO:Sn/CdS:O/CdTe/C:Cu/Ag'. To avoid the pin hole effect, the high resistive ZnO:Sn layer was deposited as a buffer layer in between the FTO and CdS:O films. It has been observed that the cell performance parameters are found to be varied with deposition power of CdO:S films and an overall conversion efficiency of 10.27% was achieved.